Professionals Talk Logistics: Sustaining Strategy and Operations : (Jon Klug and Steve Leonard (eds.)) - Welgemoed, PS (Scientia Militaria - South African Journal of Military Studies, 2026)
Professionals Talk Logistics: Sustaining Strategy and Operations edited by Jon Klug and Steve Leonard, Hampshire: Howgate, 2025, 210 pages, ISBN 978-1-9124-4067-2.